Evidence of zoonotic Poxviridae coinfections in clinically diagnosed papillomas using a newly developed mini-array test. (January 2016) - Scagliarini, Alessandra; Casà, Giovanni; Trentin, Bernadette; Gallina, Laura; Savini, Federica; Morent, Marine; Lavazza, Antonio; Puleio, Roberto; Buttaci, Calogera; Cannella, Vincenza; Purpari, Giuseppa; Di Marco, Patrizia; et al.
Our study describes a newly developed mini-array test for the rapid detection of poxviruses in animals and humans. The method is based on detection that combines target nucleic acid amplification by polymerase chain reaction and specific hybridization, using enzyme-linked antibodies, allowing identification of zoonotic orthopoxviruses and parapoxviruses in animal and human biological samples. With 100% specificity, the test rules out the possibility of cross-reactions with viral agents causing look-alike diseases. The assay was employed in the field to investigate the causes of several outbreaks of a malignant proliferative skin disease that affected domestic ruminants in Sicily during 2011–2014. Due to specific aspects of the lesions, the animals were clinically diagnosed with papillomatosis. The mini-array test allowed the identification of coinfections caused by more than 1 viral species belonging to the Parapoxvirus and Orthopoxvirus genera, either in goats or in cattle. Our study suggests that the so-called "papillomatosis" can be the result of multiple infections with epitheliotropic viruses, including zoonotic poxviruses that cannot be properly identified with classical diagnostic techniques.